Sinergi Pesantren Bustanut Tholibin dan SMP Bustanut Tholibin dalam Membangun Karakter Sosial Siswa di Era Digital - Sholikah; Alam Deny Kusuma (Journal of Practice Learning and Educational Development, 2026)
The development of digital technology has brought significant changes in the pattern of social interaction of students, including in the pesantren and school environment. This phenomenon raises problems in the form of declining manners, weakening empathy, and an increasing tendency for uncontrolled online interactions. This study aims to analyze the form of synergy between the Bustanut Tholibin Islamic Boarding School and SMP Bustanut Tholibin   in shaping the social character of students in the digital era through the perspective of Bronfenbrenner's Ecological Theory. The method used is qualitative with a case study approach, involving in-depth interviews with pesantren caregivers, teachers, and schools to gain a holistic understanding of the coaching strategies implemented by the two institutions. The results of the study show that the synergy between the two is formed through routine coordination, complementary division of roles, and the alignment of values enforced in the pesantren and school environment. The Islamic boarding school focuses on fostering manners, discipline, and direct social interaction, while SMP Bustanut Tholibin   emphasizes digital ethics education and the habit of polite communication in the online space. The discussion shows that the interaction between  the microsystem of pesantren and schools forms  a strong mesosystem, so that social values can be instilled consistently even though students are exposed to technology. The conclusion of the study emphasizes that collaboration between institutions is the main factor in the success of forming students' social character, because it is able to balance the needs of digital development with moral values that are upheld.